Short-term changes caused by fire and mowing in Brazilian Campos grasslands with different long-term fire histories - Fidelis, Alessandra Tomaselli [UNESP]; Blanco, Carolina C.; Mueller, Sandra C.; Pillar, Valerio D.; Pfadenhauer, Joerg (Wiley-Blackwell, 2012)
Questions: What are the main short- term changes in vegetation structure after fire and mowing in Campos grasslands? Are there differences in functional vegetation group responses between sites with diverse fire histories and different treatments (fire andmowing)? Location: Subtropical grasslands in Porto Alegre, Brazil, 30 03' S, 51 07' W. Methods: In two sites with different fire histories: FB - frequently burned grasslands and E - exclusion of fire for 6 yr, seven pairs of plots were examined. In each pair, fire and mowing treatments were established. Bare soil and litter cover were estimated. Vegetation releve ' s were conducted, plants identified, their cover estimated and stems counted (except for graminoids). Later, plants were grouped according to their functional group (graminoids, forbs and shrubs) for statistical analyses. Observations were conducted 30, 90 and 360 d after treatments. Results: Burned plots always showed a higher percentage of bare soil, whilst mowed plots had higher litter cover. Fire enhanced graminoid and forb cover, but did not affect shrubs. Species turnover was very high, mainly in burned plots in site FB and in mowed plots in site E. Species diversity in burned plots was the same in sites FB and E 1 yr after treatments, contrary to our hypothesis. However, in mowed plots, the number of species tended to decrease 1 yr after treatments for both sites FB and E. Conclusions: The most important short- term effect was the removal of litter and consequent opening of gaps, mostly by fire. This stimulated vegetation regeneration and provided microsites for the establishment of new species. However, fire did not enhance plant diversity, as we had hypothesized. Moreover, the disturbance history of sites should be considered, since vegetation in these sites responded differently to fire andmowing.
Keywords: Disturbance; Fire intensity; Functional groups; Subtropical grasslands; Vegetation regeneration